Laity and the Integration of the Concept of Religious Moderation in Planning Pastoral Work Programs at the Holy Trinity Parish in Paslaten - Untu, Hadi Ignatius (Ridwan Institute, 2023)
Tomohon City, as a multi-religious center with residents adhering to various religions and beliefs, is the background of this study. Christianity, with its various denominations, predominates followed by Catholicism, Islam, Buddhism, and Confucianism. This diversity affects the everyday social aspects of society and important religious events. The potential for intolerance arises without an adequate understanding of religious moderation, particularly in the face of differences in beliefs. Religious moderation is defined as religious attitudes and practices that respect diversity and differences in beliefs. Every individual believer has the militancy to uphold the truth of his religion, and the power of faith can create brotherhood and harmony in society. Religious moderation is essential for maintaining mutual respect, respect, and listening to one another, encouraging the integrity of God's creation and the common good (bonum commune). This research implements Community Service Activities (PKM) with lectures, discussions, and case study methods. The final result of PkM is a practical guide that can be adopted by participants to apply the concept of religious moderation in daily life and strengthen harmony in society. This research contributes to a further understanding of the importance of religious moderation in the face of a plurality of religions and beliefs.